Peran Dewan Perwakilan Rakyat Daerah (DPRD) terhdap Pembangunan Perekonomian Masyarakat di Kota Padang Sidimpuan - Rizki Suhandri Rambe; Anggina Siregar; Imsar Imsar (Intitut Agama Islam Nasional Laa Roiba Bogor, 2023)
DPRD is a component of government in an area that has the responsibility to oversee the implementation procedures contained in regional regulations and also statutory regulations. The fundamental problems in planning for the economic development of a region occur due to an emphasis on the strategy for carrying out the development which then has to do with the regional culture through the utilization of local (regional) human resources, institutions and physique. Qualitative techniques were applied in this study. The researcher uses a qualitative descriptive approach in conducting research by describing and explaining events, phenomena and events as they really are. The aim is to find out how DPRD institutions carry out economic development in a Padang Sidimpuan city community. In carrying out economic development, it must be based on the capacity of the population to create maximum results by utilizing available resources, creating collaboration between government agencies and private institutions, and fighting for programs that will be carried out for development in the archipelago. Keywords: DPRD, Role, Economic Development